Determination of chromium(III) ion in the soils of Almalyk MMK area of Tashkent region by sorptionspectroscopic methods (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
The soil of the area of the environmental facility Olmaliq KMK and the areas close to the KMK were analyzed by mass spectrometer method. It was found that the amount of chromium ion in the soil samples exceeded the permissible limit. Analysis of obtained results was compared with sorption-spectroscopic results. The use of organic reagents immobilized on sorbents is of practical importance for the determination of heavy metal ions in environmental objects by sorption-spectroscopic methods